Tree growth and soil fertility in plantations of genetic materials of Eucalyptus spp. (Research, Society and Development, 2021)
Were analyzed the growth and the relationship with soil fertility of genetic materials of Eucalyptus spp. planted in a non-traditional eucalyptus forestry region in Brazil. Five genetic materials were selected, two seminal: Eucalyptus urophylla and E. pellita and three clones: GFMO27, I224, and H13, planted in experimental plots in a completely randomized design. The diameter at breast height (DBH) and total height were measured; basal area and dendrometric variables were calculated, for the ages 24, 36, 48, 60, 72, and 108 months, both statistically compared. The soil was chemically characterized at 108 months of age and correlated with dendrometric variables. The growth of clones H13, I224, and GFMO 27 were superior to the E. pellita and E. urophylla. The levels of N and MO had a significant correlation with the volume and the Al+3 showed a positive correlation with DBH. Clone H13 showed higher values than the other materials, in all variables analyzed, reaching an individual volume of 1.27 m³ at 108 months. The other genetic materials (GFMO27, I244, and E. urophylla) proved to be variable in their growth behavior at different ages, and E. pellita had lower growth. The recommended genetic materials for planting are H13 and E. urophylla.